Integrated Approaches to Poverty Alleviation: Global Perspectives and Strategies - Elisabeth, Cherly (Golden Ratio of Mapping Idea and Literature Format, 2024)
This paper provides a comprehensive analysis of poverty alleviation strategies from a global perspective, synthesizing findings from diverse studies across various countries and contexts. By examining the multifaceted nature of poverty, it highlights the critical role of fulfilling basic needs, the importance of adopting locally specific solutions, and the necessity of inclusive growth and sustainable development. The paper discusses the effectiveness of community-based projects, the impact of education and health on poverty reduction, and innovative funding mechanisms such as the "energy-poverty alleviation" fund. It also explores the significant achievements and challenges of poverty alleviation efforts in countries like Nigeria and China, emphasizing the need for development-oriented strategies, legal reforms, and the involvement of multiple stakeholders in the fight against poverty. Through this analysis, the paper aims to contribute to the ongoing discourse on poverty alleviation, offering insights into successful strategies and identifying areas that require further research and policy intervention.